Mechanism for building the modern Iraqi state: Study in the royal era - Mohsin, Fatin Muhi (Al-Adab Journal, 2019)
The shape of the Iraqi state crystallized and its institutions were formed. The first features of this new entity were evident under exceptional circumstances, which was reflected in the presence of an occupying superpower that took upon itself the task of building the Iraqi state and forming its structures under a specific structure compatible with the interests of the state. At the same time, society underwent a process of restructuring and relations between its sons were formed depending on the position of the factors of production, and the features of class formations began to take shape based on whether or not they own land. The old structures of society were disintegrated, but the process of disintegration and disintegration did not go to its logical end in ending all the old forms of social structures.The new patterns formed with old ones coexisted and did not disintegrate and this coexistence was largely accompanied by ethnic and sectarian differentiation in Iraq. The factors of geographical nature have also contributed to its deepening. While fiefdoms were concentrated in the areas of southern Iraq because of their fertility, cities north of Baghdad suffered a decline in the value of handicrafts. This led to a large migration towards the main cities of Iraq and these waves of internal migration were not of a similar nature because of the different motives and the interaction of scheduling institutions with them also differed and reflected on the nature of political power and the ways of functioning and performance of state agencies. While social groups were able to establish participatory relations with each other and skillfully used state institutions to achieve their interests, the rest of society's formations benefited from the outputs of modernity and penetrated into other state institutions such as the army and civil administration, in an attempt to improve their position in the ladder of social pyramid and these institutions were later used in a coup movement seized Iraq is among the most Arab countries that have witnessed political transformations and events since the emergence of the Iraqi state in the twenties of the last century until the present. These events and transformations had the effect of building the state with the collapse of the monarchy and the establishment of the republic. It is expressed in terms of effectiveness and political stability.The paper discusses the emergence of the state in Iraq during the monarchy, and then sheds light on the role of the monarchy in the formation of social and economic structures in that era and the trends of the nascent political structures and their interaction with the new social structures, and a conclusion illustrates the outcome of the state's performance in the monarchy and its impact on the cleansing of subsequent political transformations.